Baropodometric profile of patients assisted in a physiotherapy clinic - Cunha, Francisco Valmor Macedo; Sousa, Joana D’arc Alves; Alves, Jonas Almeida (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Background: Computerized baropodometry, a posturographic recording technique used in the diagnosis and assessment of plantar pressure, which records the pressure points exerted by the body on the plantar surface, is an accurate, objective and quantitative examination. Its record is used in the diagnosis and evaluation of plantar pressure, both in static and dynamic positions. Objective: Analyze the baropodometric profile of patients in a physiotherapy clinic. Methods: A cross-sectional study of documentary character of baropodometry exams registered in the database of a physiotherapy clinic in Teresina (PI), carried out from January 2015 to December 2018. Totaling 193 exams, which include the types of feet, peak plantar pressure and correlation between peak plantar pressure with age, weight, height and BMI. The collected data were analyzed statistically by the software Win Track version 12.0, and presented through tables and figures. In this research, all ethical precepts were carried out in accordance with the resolution of the National Health Council and was approved by the ethics committee. Results: There was a higher prevalence of hollow feet (96.89%), showing a greater occurrence of displacement of the center of gravity posteriorly to the right (46.11%), it was found that there was no satisfactory correlation of anthropometric parameters with peak plantar pressure (p>0.05). Conclusion: It was possible to observe that the examinations evaluated showed a higher prevalence of hollow feet and center of gravity posteriorized to the right. In addition, there was no satisfactory correlation between peak plantar pressure with the variables age, weight, height and BMI.